Immediate mechanical stability of threaded and porous implant systems. (October 2017) - Kim, Do-Gyoon; Jeong, Yong-Hoon; Chien, Hua-Hong; Agnew, Amanda M.; Lee, Jin Whan; Wen, Hai Bo
Abstract: Background: Primary stability of a dental implant system is an essential factor to maintain its long-term success. Thus, the objective of this study was to examine whether primary stability is different between threaded and porous dental implant systems placed in artificial bone blocks and human cadaveric mandibular bone. Materials and methods: Forty-two threaded and 42 highly porous dental implants were placed in artificial polyurethane bone foams with 7 different thicknesses (3.5 to 12 mm). In addition, 11 threaded and 11 porous implants were installed in 8 edentulous mandibles of human cadavers. Implant stability quotient values, insertion torque, static and dynamic stiffness, and viscoelastic tan δ of each implant system were measured. Mean gray values were obtained at the implantation sites in the human mandible. Findings: The porous implant group had substantially lower implant stability quotient values and insertion torque values than the threaded implant group that were equal or > 5.5 mm in thickness of the artificial bone block ( p  < 0.026) with the exception of 8.5 mm thickness, while static and dynamic stiffness values were not different between the two implant groups greater than 5.5 mm in thickness ( p  > 0.132). Static and dynamic stiffness values of the porous group were significantly greater than the thread group in the human mandibular bone ( p  < 0.015). Interpretation: The porous layer supports axial loading better than lateral and shear loading of the dental implant system. This result indicates that trabecular shaped architecture of the porous layer may provide sufficient anchorage compromising reduction of the axial primary stability of the porous implant system to be comparable with the threaded implant system. Highlights: Porous layer supports axial loading better than shear loading of the implant system. Stiffness of the porous implant system was greater than that of the threaded implant system. Trabecular shaped architecture of the porous layer may provide sufficient anchorage.